The Spectrophotometric Determination of Olanzapine via Coupling with Diazotized p-Nitroaniline - R. Fadhel, Sahar; I. Abdulla, Najwa; D. Sulaiman, Intidhar (Iraqi Journal of Pharmaceutical Sciences, 2017)
A new spectrophotometric method has been developed for the assay of olanzapine (OLN.) in pure and dosage forms. The method is based on the diazocoupling of (OLN.) with diazotized p-nitroaniline in alkaline medium to form a stable brown colored water-soluble azo dye with a maximum absorption at 405 nm. The variables that affect the completion of reaction have been carefully optimized. Beer’s law is obeyed over the concentration range of (0.5-45.0 μg.mL-1) with a molar absorptivity of 1.5777×104 L.mol-1.cm-1. The limit of detection was 0.3148 μg.mL-1 and Sandell’s sensitivity value was 0.0198 μg.cm-2. The proposed method has been applied successfully to the determination of olanzapine in tablet pharmaceutical preparations.Keywords: Spectrophotometry, Olanzapine, Diazotization, p-nitroaniline, tablet dosage form.